Case Report: A novel t(15;17)(q24;q11.2) translocation involving NF1::SCAMP5 fusion in a patient with myeloproliferative neoplasms - Chang, Yuying; Chen, Yakun; Zhao, Weiwei; Shen, Guomin; Guo, Sujuan; Wang, Wei (Frontiers in Oncology, 2025)
Myeloproliferative neoplasms (MPNs) are a heterogeneous group of disorders characterized by the abnormal proliferation of terminally differentiated myeloid cells. While cytogenetic abnormalities such as t(15;17) are documented in MPNs, the specific translocation resulting in NF1::SCAMP5 fusion has not been previously reported. Here we present a 69-year-old female patient with anemia and splenomegaly, exhibiting CALR exon 9 mutation (c.1099_1150del52) and JAK2 V617F negativity. Cytogenetic analysis revealed t(15;17)(q24;q11.2), distinct from the classical APL-associated t(15;17)(q22;q21), with RNA-Seq confirming a novel NF1::SCAMP5 fusion. Bone marrow biopsy showed MF-1 fibrosis and megakaryocyte depletion, deviating from typical primary myelofibrosis histology. The patient achieved stable disease post-ruxolitinib treatment. This case highlights a unique molecular-pathological profile, suggesting NF1::SCAMP5 may define a provisional MPN subtype with distinct genetic features, warranting further study to elucidate its clinical significance.